TEACHING ENGLISH WITH PICTURE BOOKS: CURRENT CHALLENGES AND POSSIBLE SOLUTIONS IN ENGLISH EDUCATION IN JAPAN - Kochiyama, Arisa (UPI Press, 2016)
The council for revitalization of education has submitted a proposal to Prime Minister Shinzo Abe for educational reforms to make English language courses compulsory in the fifth and sixth grades. The majority of elementary school teachers are now worried and lacking in confidence to teach English, as they feel they are ill-equipped for their new role as language instructors. According to Keith Schoch’s article Picture Books across the Curriculum, picture books deserve a place in the upper elementary and middle school grades for a number of reasons: If chosen with consideration for the interests of the students and used in ways that are appropriate for learners, picture books can provide valuable opportunities of language-rich experiences and interactions. Thus, the present study firstly describes and analyses some of the challenges facing English education in Japan by relating to its wider social setting. Secondly, the study analyzes how teachers perceive they can promote language learning in their EFL classrooms through the medium of picture books. Thirdly, the study discusses the merits of using picture books in the upper elementary and middle school English education from the viewpoint of English language learning, and then investigates topics and themes of a picture book which illuminate some universal aspects of human condition.